Pemanfaatan Limbah Kulit Telur Menjadi Suplemen Penambah Gizi Bagi Masyarakat di Desa Paddingin Kecamatan Sanrobone Kabupaten Takalar - Syamsul Bakhri; Muhammad Azhar; Andi Widya Mufila Gaffar; Siti Nurana; Nur Ilah Padhila; Fadil Abdillah; Muhammad Ridha Kasim (PT.Mantaya Idea Batara, 2021)
Empowerment of rural communities, especially the community of partner villages or assisted villages, is a community service carried out by Universitas Muslim Indonesia Lecturers as a form of the Tri Dharma of higher education. One of the partner villages or villages assisted by the Universitas Muslim Indonesia where we serve, is Paddingin Village, Sanrobone District, Takalar Regency, where one of our service programs is to provide counseling to village communities about the use of eggshell waste as nutritional supplements. In addition to being easy to obtain and cheap to process, eggshells have a high content of calcium so that the flour produced from processing eggshells can be used as a supplement to increase the nutrition of rural communities